Theoretical fundamentals of financial health of the enterprise - Nozimov Eldor Anvarovich (Indonesian Journal of Innovation Studies, 2020)
This article highlights the importance of financial well-being in enterprises, the importance of organizing it on the basis of legal documents, diagnosing the economic situation of insolvent enterprises, and improving the business environment in a competitive environment.